Leveraging Power Line Communications for Grid Intelligence: A Comprehensive Review of Signal-Based Techniques to Infer Grid Information - Javier Hernandez Fernandez; Abdulah Jarouf; Aymen Omri; Roberto Di Pietro (IEEE Access)
High-frequency signals were widely studied in the last decade to identify grid and channel conditions in power lines. Power Line Modems (PLMs) operating on the grid’s physical layer are capable of transmitting such signals to infer information about the medium. When applied to the electrical grid, one of the key advantages of Power Line Communication (PLC) is its capacity to use signals to provide information about the grid itself. This makes PLC an ideal communication technology for smart grid applications, with significant potential for expanding its use in the realm of grid monitoring and surveillance. In this paper, we focus on PLC grid information inference and provide several contributions: a classification of PLC-based applications, a review of the relevant literature, and insights to further advance the field. Our research identified contributions addressing PLMs for three main grid information inference applications: topology inference, anomaly detection, and grid cybersecurity. We utilize the outcome of our review to shed light on the current limitations of the research contributions and suggest future research directions in this field.